2015
DOI: 10.1016/j.mex.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A simple and effective method to encapsulate tobacco mesophyll protoplasts to maintain cell viability

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
2
21
0
2
Order By: Relevance
“…Growth, directionality and compatibility was observed for Brachypodium seeds on all three PDMS punched molds and the results were in line with the previous reports conducted with Nicotiana and Arabidopsis [14,19,20]. After several experiments, we concluded that after 4 days of vernalization and 2 DAG seedling stage, the seedling had to be inserted in the correct orientation in the chip to make it grow along the length of the narrow 1mm channel.…”
Section: Discussionsupporting
confidence: 90%
“…Growth, directionality and compatibility was observed for Brachypodium seeds on all three PDMS punched molds and the results were in line with the previous reports conducted with Nicotiana and Arabidopsis [14,19,20]. After several experiments, we concluded that after 4 days of vernalization and 2 DAG seedling stage, the seedling had to be inserted in the correct orientation in the chip to make it grow along the length of the narrow 1mm channel.…”
Section: Discussionsupporting
confidence: 90%
“…Physically, this means that the energy barrier for nanoparticle transport across protoplast membrane is lower, as reflected in the lower critical zeta potential value for nanoparticle penetration into protoplast interior compared to that required to traverse chloroplast double lipid bilayers ( Figure ). Furthermore, without the protection of plant cell wall, the protoplast membrane is known to be delicate and easily ruptured due to external handling such as electroporation and bombardment of nanoparticles . This was not accounted for by the existing LEEP model, which only predicts the minimum surface charge that a nanoparticle of certain size has to possess in order to traffic past the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The centrifugation and resuspension process was repeated three times to achieve high purity of viable protoplasts. The viability of protoplasts was determined by staining the protoplasts with FDA, as described elsewhere . The total protoplasts yield was determined by a hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol for apple protoplast preparation was similar to that for the grapevine, except for the addition of hemicellulase to the cell-wall digestion enzyme solution (1–2%). The viability and density of grape and apple protoplast were determined using a haemocytometer, by staining the protoplast with fluorescein diactetate (FDA) as described elsewhere (Lei et al, 2015). At least two biological replications and three technical replication sets were used to optimize and measure enzyme concentration and protoplast yield.…”
Section: Methodsmentioning
confidence: 99%